Cellulose nanofiber composite

The integration of cellulose nanofibers with cellulose derivatives like hydroxyalkylcellulose enhances dispersibility in organic solvents, addressing the limitations of existing methods by maintaining the nanofibers' structure and expanding their application scope.

JP2025007985APending Publication Date: 2025-01-20FUJIKURA COMPOSITES INC +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023109780
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing cellulose nanofibers face challenges in achieving uniform dispersion in organic solvents due to their hydrophilic nature, limiting their application scope, and existing modification methods are complex and alter the molecular structure, making them difficult to use effectively.

Method used

A cellulose nanofiber composite is formed by integrating cellulose nanofibers with a cellulose derivative, such as hydroxyalkylcellulose, through physical adsorption, maintaining the nanofibers' structure while enhancing dispersibility in organic solvents.

Benefits of technology

The composite achieves excellent dispersibility and handling properties in organic solvents, allowing for broader application without the need for prior modification, ensuring the nanofibers' molecular structure is preserved and aggregation is minimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007985000002
    Figure 2025007985000002
  • Figure 2025007985000003
    Figure 2025007985000003
  • Figure 2025007985000004
    Figure 2025007985000004
Patent Text Reader

Abstract

To provide a cellulose nanofiber composite having excellent dispersibility of a cellulose nanofiber in an organic solvent and handleability in an organic solvent, which can easily expand the range of application of the cellulose nanofiber.SOLUTION: There is provided a cellulose nanofiber composite containing a cellulose nanofiber and a cellulose derivative, wherein the cellulose nanofiber and the cellulose derivative are integrated into a solid phase cellulose nanofiber composite.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nanocellulose composite, and in particular to a cellulose nanofiber composite that also exhibits affinity for hydrophobic substances. [Background technology]

[0002] Nanocellulose is a cellulose fiber with a thickness on the order of nanometers. Nanocellulose is obtained, for example, by defibrating plant fibers such as pulp in an aqueous medium. Nanocellulose is classified into cellulose nanofibers, cellulose crystals, cellulose whiskers, bacterial cellulose, etc., depending on the structured cellulose of nanocellulose. Cellulose nanofibers are lightweight and strong, and therefore have attracted attention for use as a reinforcing material for thermoplastic resins, etc. (see, for example, Patent Document 1).

[0003] On the other hand, since cellulose nanofibers are hydrophilic, it is difficult to disperse them uniformly in organic solvents, and the range of application is limited. Therefore, it has been proposed to impart hydrophobicity to cellulose nanofibers by reacting cellulose nanofibers in a water-containing state with vinyl organic acid and then recovering the product, thereby improving dispersibility in organic solvents (see, for example, Patent Document 2). Hereinafter, cellulose nanofibers obtained by imparting desired properties such as hydrophobicity to naturally derived cellulose nanofibers obtained from plant fibers, etc., may be referred to as "modified cellulose nanofibers."

[0004] However, the modified cellulose nanofibers shown in Patent Document 2 have problems in that the reaction conditions between the cellulose nanofibers and the vinyl organic acid are strict and the production process is complicated. Furthermore, in the modified cellulose nanofibers modified with the vinyl organic acid shown in Patent Document 2, the molecular structure of the cellulose nanofiber skeleton itself changes depending on the degree of modification, and there is room for improvement in terms of improving the hydrophobicity of the modified cellulose nanofibers and, in turn, in terms of improving the dispersibility in organic solvents. Therefore, the modified cellulose nanofibers shown in Patent Document 2 need to be improved in terms of obtaining a dispersion liquid with excellent dispersibility of cellulose nanofibers, and there is still a problem in that the application range of cellulose nanofibers is limited.

[0005] Furthermore, as a technology for imparting hydrophobicity to cellulose nanofibers, it has been proposed to modify cellulose nanofibers to be hydrophobic with a small mass of modifying groups by binding two types of modifying groups to the surface of cellulose nanofibers: one selected for wettability, such as an aromatic group, and the other selected for steric repulsion and hydrophobicity, such as a polyalkylene glycol group. However, modified cellulose nanofibers modified with two types of modifying groups, such as an aromatic group and a polyalkylene glycol group, have a complex chemical structure, and there is still a need for improvement in terms of obtaining a dispersion with excellent dispersibility of cellulose nanofibers. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-11392 A [Patent Document 2] International Publication No. 2016 / 010016 Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above circumstances, an object of the present invention is to provide a cellulose nanofiber composite that has excellent dispersibility in organic solvents and handleability in organic solvents, and can easily expand the range of applications of cellulose nanofibers. [Means for solving the problem]

[0008] The gist of the configuration of the present invention is as follows. [1] A cellulose nanofiber composite comprising a cellulose nanofiber and a cellulose derivative, the cellulose nanofiber being integrated with the cellulose derivative in a solid phase. [2] The solid-phase cellulose nanofiber composite described in [1], in which the cellulose derivative is physically adsorbed and integrated onto the cellulose nanofiber. [3] A solid-phase cellulose nanofiber composite according to [1] or [2], in which the cellulose nanofiber in a dry state and the cellulose derivative are integrated. [4] A solid-phase cellulose nanofiber composite according to [1] or [2], containing 5.0 parts by mass or more and 5,000 parts by mass or less of the cellulose derivative per 100 parts by mass of the cellulose nanofiber. [5] The cellulose nanofiber composite according to [1] or [2], containing 10 parts by mass or more and 2,000 parts by mass or less of the cellulose derivative per 100 parts by mass of the cellulose nanofiber. [6] A solid-phase cellulose nanofiber composite according to [1] or [2], wherein the standard deviation in a transmittance test for light with a wavelength of 400 nm measured every 2 seconds over a period of 180 seconds for the solid-phase cellulose nanofiber composite containing 10 parts by mass or more and 2,000 parts by mass or less of the cellulose derivative per 100 parts by mass of the cellulose nanofiber is 0.10 or less. [7] The solid-phase cellulose nanofiber composite according to [1] or [2], wherein the cellulose derivative comprises at least one selected from the group consisting of hydroxyalkyl cellulose and alkyl cellulose. [8] The solid-phase cellulose nanofiber composite according to [1] or [2], wherein the cellulose derivative is hydroxyalkyl cellulose. [9] The solid-phase cellulose nanofiber composite according to [8], wherein the hydroxyalkyl cellulose is hydroxypropyl cellulose.

[0009] The cellulose nanofibers, which are components of the cellulose nanofiber composite, the solid phase of [1], are not modified cellulose nanofibers that have been given desired properties such as hydrophobicity (hereinafter, cellulose nanofibers that are not modified cellulose nanofibers may be simply referred to as "cellulose nanofibers"). In other words, the cellulose nanofibers themselves, which are components of the cellulose nanofiber composite, have a hydrophilic chemical structure. Note that cellulose nanofibers have an average fiber diameter of less than 1.0 μm, that is, cellulose fibers with an average fiber diameter on the nano order.

[0010] In addition, the cellulose derivative, which is a component of the cellulose nanofiber composite, which is the solid phase of [1], is integrated with the cellulose nanofiber, which is a hydrophilic chemical structure, in the cellulose nanofiber composite. When the cellulose nanofiber composite, which is the solid phase, is dispersed in an organic solvent, the hydroxyl groups of the cellulose derivative and the hydroxyl groups of the cellulose nanofiber interact with each other, resulting in a state in which the cellulose derivative is coordinated to the cellulose nanofiber.

[0011] In addition, in the above embodiment, "transmittance test of light with a wavelength of 400 nm measured every 2 seconds over a period of 180 seconds" refers to a test in which a dispersion of a cellulose nanofiber composite in which 0.01 g to 2.0 g of cellulose derivative is integrated with 0.1 g of cellulose nanofiber is added to 20 ml of tetrahydrofuran (dispersion medium) so that the cellulose nanofiber is 0.1 g, and 2.0 ml of the dispersion is poured into a 4.5 ml container under conditions of 25°C, and stirred at a rotation speed of 1000 rpm using a stirrer (stirring means) with a diameter of 9 mm and a height of 6.5 mm. The transmittance is measured at the center of the height of the dispersion of the cellulose nanofiber composite every 2 seconds over a period of 180 seconds from the start of stirring, and the average transmittance of the transmittance of each measurement time is calculated, and this test measures the transmittance of light with a wavelength of 400 nm over an optical path length of 1 cm. In addition, in the above embodiment, the "standard deviation in the transmittance test" refers to the average value of each standard deviation (n=3) obtained from one measurement of the average transmittance, that is, the standard deviation of the transmittance measured every 2 seconds over a period of 180 seconds from the start of stirring, calculated from three measurements of the average transmittance. Effect of the Invention

[0012] According to the solid-phase cellulose nanofiber composite of the present invention, the cellulose nanofibers, which are components of the solid-phase cellulose nanofiber composite, have excellent dispersibility in a dispersion medium due to the integration of the cellulose nanofibers with the cellulose derivative, and the solid-phase cellulose nanofiber composite of the present invention has handleability in an organic solvent. The solid-phase cellulose nanofiber composite of the present invention has excellent dispersibility in a dispersion medium such as an organic solvent even if it is not a modified cellulose nanofiber that has been given properties such as hydrophobicity, so that a composition having excellent dispersibility of the cellulose nanofiber can be easily obtained by adding it to a dispersion medium. Therefore, with the solid-phase cellulose nanofiber composite of the present invention, the dispersion of the cellulose nanofiber in the hydrophobic substance to which it is applied can be easily and uniformly achieved, and the range of application of the cellulose nanofiber can be easily expanded.

[0013] Furthermore, with the solid-phase cellulose nanofiber composite of the present invention, there is no need to modify the cellulose nanofibers to be hydrophobic in advance, and the skeleton of the cellulose nanofiber is maintained, so that the properties of the cellulose nanofiber can be reliably imparted to the subject of application.

[0014] Furthermore, according to the solid-phase cellulose nanofiber composite of the present invention, the cellulose derivative is physically adsorbed and integrated onto the cellulose nanofiber, thereby further reliably improving the dispersibility of the cellulose nanofiber in a dispersion medium such as an organic solvent.

[0015] Furthermore, according to the solid-phase cellulose nanofiber composite of the present invention, the cellulose nanofibers in a dry state are integrated with the cellulose derivative, thereby further reliably improving the dispersibility of the cellulose nanofibers in a dispersion medium such as an organic solvent.

[0016] Furthermore, according to the solid-phase cellulose nanofiber composite of the present invention, by containing 5.0 parts by mass or more and 5000 parts by mass or less of a cellulose derivative per 100 parts by mass of cellulose nanofibers, excellent dispersibility of the cellulose nanofibers can be reliably obtained in a dispersion medium such as an organic solvent. Furthermore, according to the solid-phase cellulose nanofiber composite of the present invention, by containing 10 parts by mass or more and 2000 parts by mass or less of a cellulose derivative per 100 parts by mass of cellulose nanofibers, excellent dispersibility of the cellulose nanofibers can be further reliably obtained in a dispersion medium such as an organic solvent.

[0017] Furthermore, according to the solid-phase cellulose nanofiber composite of the present invention, the cellulose derivative contains at least one type selected from the group consisting of hydroxyalkyl cellulose and alkyl cellulose, thereby ensuring excellent dispersibility of the cellulose nanofiber in a dispersion medium such as an organic solvent.

[0018] Furthermore, in the solid-phase cellulose nanofiber composite of the present invention, the cellulose derivative is hydroxyalkyl cellulose, which more reliably improves the dispersibility of the cellulose nanofibers in a dispersion medium such as an organic solvent.

[0019] Furthermore, in the solid-phase cellulose nanofiber composite of the present invention, the hydroxyalkyl cellulose is hydroxypropyl cellulose, which further reliably improves the dispersibility of the cellulose nanofibers in a dispersion medium such as an organic solvent. [Brief description of the drawings]

[0020] [Figure 1] Photographs showing the dispersibility of solid-phase cellulose nanofiber composites in Comparative Example 1 (left), Example 1 (center), and Example 2 (right). [Diagram 2] Photographs showing the dispersibility of solid-phase cellulose nanofiber composites in Comparative Example 1 (left), Example 3 (center), and Example 4 (right). [Diagram 3] Photographs showing the dispersibility of solid-phase cellulose nanofiber composites in Comparative Example 1 (left), Example 5 (center), and Example 6 (right). [Figure 4] Photographs showing the dispersibility of solid-phase cellulose nanofiber composites in Comparative Example 1 (left) and Example 7 (right). [Diagram 5] 1 is a photograph showing the dispersibility of cellulose nanofibers in Reference Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] <Solid-phase cellulose nanofiber composite> The solid-phase cellulose nanofiber composite of the present invention contains cellulose nanofibers and a cellulose derivative, and the cellulose nanofibers and the cellulose derivative are integrated. The solid-phase cellulose nanofiber composite of the present invention is a single material in which the cellulose nanofibers and the cellulose derivative are integrated. For example, the solid-phase cellulose nanofiber composite of the present invention is a composite material in which the cellulose nanofibers and the cellulose derivative are bonded by intermolecular forces such as van der Waals forces and hydrogen bonds. From the above, the solid-phase cellulose nanofiber composite of the present invention is not a mixture in which the solid-phase cellulose nanofibers and the solid-phase cellulose derivatives are simply mixed together.

[0022] An example of an embodiment in which the cellulose nanofibers and the cellulose derivative are integrated is a embodiment in which the cellulose derivative is physically adsorbed to the cellulose nanofibers. Specifically, for example, the cellulose nanofibers and the cellulose derivative are integrated by the cellulose derivative being physically adsorbed to the cellulose nanofibers in a chain form along the surface of the cellulose nanofibers.

[0023] In the solid-phase cellulose nanofiber composite of the present invention, for example, cellulose nanofibers in a dry state and a cellulose derivative are integrated. Along the surface of the cellulose nanofiber in a dry state, a chain-like cellulose derivative in a dry state is physically adsorbed to the cellulose nanofiber. An example of an embodiment in which the cellulose nanofiber in a dry state and the cellulose derivative are integrated is an embodiment in which freeze-dried cellulose nanofibers and a cellulose derivative are integrated. From the above, an example of the shape of the solid-phase cellulose nanofiber composite of the present invention is a cotton-like shape.

[0024] The solid-phase cellulose nanofiber composite of the present invention may, for example, be in a form in which at least a portion of the cellulose derivative is wound around the cellulose nanofiber. Specifically, for example, the solid-phase cellulose nanofiber composite may be in a form in which at least a portion of the cellulose derivative is physically adsorbed to the cellulose nanofiber while being wound around the surface of the cellulose nanofiber. Further, the solid-phase cellulose nanofiber composite of the present invention may, for example, be in a form in which the entire cellulose derivative is physically adsorbed to the cellulose nanofiber, or in a form in which the end of the cellulose derivative is physically adsorbed to the cellulose nanofiber. From the viewpoint of physical adsorption to the cellulose nanofiber, the cellulose derivative is preferably a chain-like cellulose derivative.

[0025] In the solid-phase cellulose nanofiber composite of the present invention, the cellulose nanofibers and the cellulose derivative are integrated, so that aggregation of the cellulose nanofibers is suppressed, and when the solid-phase cellulose nanofiber composite is added to a dispersion medium such as an organic solvent, the cellulose nanofibers have excellent dispersibility in the dispersion medium. In addition, the solid-phase cellulose nanofiber composite of the present invention has handleability in an organic solvent. That is, the solid-phase cellulose nanofiber composite of the present invention has excellent dispersibility in a dispersion medium such as an organic solvent even if it is not a modified cellulose nanofiber to which characteristics such as hydrophobicity have been imparted, so that a composition having excellent dispersibility of the cellulose nanofibers can be easily obtained by adding the solid-phase cellulose nanofiber composite to a dispersion medium. Therefore, in the solid-phase cellulose nanofiber composite of the present invention, the dispersion of the cellulose nanofibers in the hydrophobic substance to which the solid-phase cellulose nanofiber composite is applied can be easily and uniformly achieved, so that the range of application of the cellulose nanofibers can be easily expanded. In addition, since the solid-phase cellulose nanofiber composite of the present invention does not require the cellulose nanofibers to be modified to be hydrophobic in advance, the skeleton of the cellulose nanofiber is maintained, and the characteristics of the cellulose nanofiber can be reliably imparted to the application target.

[0026] In particular, in the solid-phase cellulose nanofiber composite of the present invention, the cellulose derivative is integrated in a state where it is physically adsorbed onto the cellulose nanofiber, which more reliably suppresses aggregation of the cellulose nanofiber, and more reliably improves the dispersibility of the cellulose nanofiber in a dispersion medium such as an organic solvent.

[0027] In particular, in the solid-phase cellulose nanofiber composite of the present invention, the cellulose nanofibers in a dry state are integrated with the cellulose derivative, which more reliably suppresses aggregation of the cellulose nanofibers, thereby more reliably improving the dispersibility of the cellulose nanofibers in a dispersion medium such as an organic solvent.

[0028] The dispersion characteristics of the solid-phase cellulose nanofiber composite can be confirmed by measuring the standard deviation of the transmittance test of light with a wavelength of 400 nm measured every 2 seconds over 180 seconds for the composition obtained by dispersing the solid-phase cellulose nanofiber composite of the present invention in a dispersion medium. In a composition obtained by dispersing a solid-phase cellulose nanofiber composite in a dispersion medium, the lower the dispersibility of the cellulose nanofibers, and therefore the more easily the cellulose nanofibers are in a state of aggregation, the lower the uniform dispersion of the cellulose nanofibers in the composition, and therefore the higher the standard deviation of the transmittance test of light with a wavelength of 400 nm measured every 2 seconds over 180 seconds. On the other hand, in a composition obtained by dispersing a solid-phase cellulose nanofiber composite in a dispersion medium, the lower the aggregation state of the cellulose nanofibers and the more uniform the dispersion of the cellulose nanofibers is, and therefore the higher the dispersion stability of the cellulose nanofibers is, and therefore the lower the standard deviation of the transmittance test of light with a wavelength of 400 nm measured every 2 seconds over 180 seconds.

[0029] The standard deviation in a transmittance test of light with a wavelength of 400 nm measured every 2 seconds over a period of 180 seconds for a composition obtained by dispersing in a dispersion medium a solid-phase cellulose nanofiber composite containing 10 to 2,000 parts by mass of a cellulose derivative per 100 parts by mass of cellulose nanofiber is preferably 0.10 or less, more preferably 0.05 or less, in order to ensure that the solid-phase cellulose nanofiber composite has excellent dispersibility, and is even more preferably 0.02 or less, and particularly preferably 0.01 or less, in order to ensure that the solid-phase cellulose nanofiber composite has even better dispersibility.

[0030] In addition, the dispersion characteristics of the solid-phase cellulose nanofiber composite can be confirmed by measuring the transmittance of the composition obtained by dispersing the solid-phase cellulose nanofiber composite of the present invention in a dispersion medium in a transmittance test of light with a wavelength of 400 nm measured every 2 seconds over 180 seconds. In a composition obtained by dispersing a solid-phase cellulose nanofiber composite in a dispersion medium, the lower the dispersibility of the cellulose nanofibers, and therefore the more easily the cellulose nanofibers are in a state of aggregation, the lower the uniform dispersion of the cellulose nanofibers in the composition, and therefore the higher the transmittance in the transmittance test of light with a wavelength of 400 nm measured every 2 seconds over 180 seconds. On the other hand, in a composition obtained by dispersing a solid-phase cellulose nanofiber composite in a dispersion medium, the lower the aggregation state of the cellulose nanofibers and the more uniform the dispersion of the cellulose nanofibers, and therefore the higher the dispersion stability of the cellulose nanofibers, and therefore the lower the transmittance in the transmittance test of light with a wavelength of 400 nm measured every 2 seconds over 180 seconds.

[0031] The term "transmittance" refers to an average transmittance calculated from the transmittance at each measurement time, which is measured every 2 seconds over 180 seconds from the start of stirring in a transmittance test for light with a wavelength of 400 nm, measured every 2 seconds over 180 seconds. The term "average transmittance" refers to the average of three measurements of the average transmittance.

[0032] The average transmittance of a composition obtained by dispersing in a dispersion medium a solid-phase cellulose nanofiber composite containing 10 to 2000 parts by mass of a cellulose derivative per 100 parts by mass of cellulose nanofibers, measured every 2 seconds over a period of 180 seconds, is preferably 0.50% or less, more preferably 0.40% or less, because the solid-phase cellulose nanofiber composite is reliably provided with excellent dispersibility, and particularly preferably 0.30% or less, because the solid-phase cellulose nanofiber composite is reliably provided with even more excellent dispersibility. The lower limit of the average transmittance is, for example, 0.10%.

[0033] The ratio of the cellulose derivative in the solid-phase cellulose nanofiber composite of the present invention is not particularly limited, but the lower limit is preferably 5.0 parts by mass per 100 parts by mass of cellulose nanofibers, from the viewpoint of reliably obtaining excellent dispersibility of the cellulose nanofibers in a dispersion medium such as an organic solvent, more preferably 10 parts by mass, from the viewpoint of further reliably obtaining excellent dispersibility of the cellulose nanofibers in a dispersion medium such as an organic solvent, and more preferably 100 parts by mass, from the viewpoint of further improving the dispersibility of the cellulose nanofibers in a dispersion medium such as an organic solvent. On the other hand, the upper limit of the ratio of the cellulose derivative is preferably 5000 parts by mass per 100 parts by mass of cellulose nanofibers, from the viewpoint of reliably obtaining excellent dispersibility of the cellulose nanofibers in a dispersion medium such as an organic solvent while reliably imparting the properties of the cellulose nanofibers to the application target, and more preferably 4000 parts by mass, more preferably 3000 parts by mass, and particularly preferably 2000 parts by mass, from the viewpoint of further reliably obtaining excellent dispersibility of the cellulose nanofibers in a dispersion medium such as an organic solvent.

[0034] <Cellulose nanofiber> The cellulose nanofibers, which are components of the solid-phase cellulose nanofiber composite of the present invention, are described in detail below. The cellulose nanofibers, which are components of the solid-phase cellulose nanofiber composite of the present invention, are not modified cellulose nanofibers that have been given desired properties such as hydrophobicity, but are hydrophilic cellulose nanofibers that have not been modified. Therefore, when producing a solid-phase cellulose nanofiber composite, it is not necessary to modify the cellulose nanofibers to give them desired properties such as hydrophobicity.

[0035] The cellulose nanofiber has an average fiber diameter of less than 1.0 μm. As long as the cellulose nanofiber has an average fiber diameter of less than 1.0 μm, the size of the cellulose is not particularly limited, but from the viewpoint of expanding the range of application of the cellulose nanofiber, the average fiber diameter is preferably 4 nm or more and 100 nm or less, and particularly preferably 10 nm or more and 50 nm or less. The average fiber length of the cellulose nanofiber is not particularly limited, but from the viewpoint of expanding the range of application of the cellulose nanofiber, it is preferably 20 μm or more and 200 μm or less, and particularly preferably 50 μm or more and 150 μm or less. The average fiber diameter of the cellulose can be measured, for example, by a scanning probe microscope, a nitrogen adsorption method, or the like. The average fiber length of the cellulose can be measured by an electron microscope (transmission electron microscope (TEM), scanning electron microscope (SEM)), a scanning probe microscope, or the like.

[0036] An example of the cellulose nanofiber is cellulose derived from a natural product. Specifically, an example of the cellulose nanofiber is a nanofiber obtained by subjecting a cellulose precursor derived from a natural product, which is used as a raw material, to a defibration treatment. An example of the cellulose precursor, which is the raw material of the cellulose nanofiber, is plant fiber such as pulp.

[0037] <Cellulose derivatives> The cellulose derivative, which is a component of the solid-phase cellulose nanofiber composite of the present invention, is a compound obtained by chemically modifying cellulose, and is therefore a different component from cellulose nanofibers. The cellulose derivative is integrated with the cellulose nanofibers in the solid-phase cellulose nanofiber composite of the present invention.

[0038] In addition, when the solid-phase cellulose nanofiber composite of the present invention is added to a dispersion medium such as an organic solvent, the cellulose derivative dissolves in the dispersion medium, and the hydroxyl groups of the cellulose derivative and the hydroxyl groups of the cellulose nanofiber interact with each other, resulting in a state in which the cellulose derivative is coordinated to the cellulose nanofiber. In addition, since both cellulose nanofibers and cellulose derivatives have a cellulose skeleton, their molecular structures are similar. Therefore, since the cellulose nanofiber has a high affinity with the cellulose derivative, it is considered that the cellulose derivative is likely to be coordinated to the cellulose nanofiber. By achieving a state in which the cellulose derivative is coordinated to the cellulose nanofiber, the surface activity of the cellulose derivative is exerted, and the cellulose nanofiber has excellent dispersibility in the dispersion medium.

[0039] In addition, the solid-phase cellulose nanofiber composite of the present invention uses a cellulose derivative, which is a biocompatible material, thereby ensuring safety to the human body. In addition, it is possible to utilize forest resources such as thinned wood, thereby reducing the environmental burden.

[0040] The cellulose derivative is not particularly limited as long as it is a derivative obtained by chemically reacting at least a portion of the hydroxyl groups of cellulose, and examples thereof include hydroxyalkyl cellulose, alkyl cellulose, carboxyalkyl cellulose, hydroxyalkyl alkyl cellulose, etc. Among these, hydroxyalkyl cellulose and alkyl cellulose are preferred because excellent dispersibility of the cellulose nanofibers can be reliably obtained in the dispersion medium when the solid-phase cellulose nanofiber composite of the present invention is added to a dispersion medium such as an organic solvent, and hydroxyalkyl cellulose is particularly preferred because the dispersibility of the cellulose nanofibers is more reliably improved in the dispersion medium. The above-mentioned cellulose derivatives may be used alone or in combination of two or more kinds.

[0041] Examples of hydroxyalkyl cellulose include hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxybutyl cellulose, hydroxypentyl cellulose, and hydroxyhexyl cellulose. Among these, hydroxyethyl cellulose and hydroxypropyl cellulose are preferred, and hydroxypropyl cellulose is particularly preferred, since the dispersibility of the cellulose nanofibers in the dispersion medium is further improved when the solid-phase cellulose nanofiber composite of the present invention is added to a dispersion medium such as an organic solvent. The above-mentioned hydroxyalkyl celluloses may be used alone or in combination of two or more.

[0042] Examples of alkyl cellulose include methyl cellulose, ethyl cellulose, propyl cellulose, butyl cellulose, pentyl cellulose, and hexyl cellulose. Among these, methyl cellulose and ethyl cellulose are preferred, and ethyl cellulose is particularly preferred, because when the solid-phase cellulose nanofiber composite of the present invention is added to a dispersion medium such as an organic solvent, the dispersibility of the cellulose nanofibers in the dispersion medium is reliably obtained. The above alkyl celluloses may be used alone or in combination of two or more kinds.

[0043] Examples of the carboxyalkyl cellulose include carboxymethyl cellulose, carboxyethyl cellulose, carboxypropyl cellulose, carboxybutyl cellulose, carboxypentyl cellulose, carboxyhexyl cellulose, etc. The above-mentioned carboxyalkyl celluloses may be used alone or in combination of two or more kinds.

[0044] Hydroxyalkyl alkyl cellulose is a cellulose having hydroxyalkyl and alkyl. Examples of hydroxyalkyl alkyl cellulose include cellulose having hydroxymethyl and alkyl such as hydroxymethyl methyl cellulose, hydroxymethyl ethyl cellulose, hydroxymethyl propyl cellulose, and hydroxymethyl butyl cellulose; cellulose having hydroxyethyl and alkyl such as hydroxyethyl methyl cellulose, hydroxyethyl ethyl cellulose, hydroxyethyl propyl cellulose, and hydroxyethyl butyl cellulose; cellulose having hydroxypropyl and alkyl such as hydroxypropyl methyl cellulose, hydroxypropyl ethyl cellulose, hydroxypropyl propyl cellulose, and hydroxypropyl butyl cellulose; cellulose having hydroxybutyl and alkyl such as hydroxybutyl methyl cellulose, hydroxybutyl ethyl cellulose, hydroxybutyl propyl cellulose, and hydroxybutyl butyl cellulose. The above-mentioned hydroxyalkyl alkyl cellulose may be used alone or in combination of two or more kinds.

[0045] <Composition obtained by dispersing solid-phase cellulose nanofiber composite in a dispersion medium> The composition obtained by dispersing the solid-phase cellulose nanofiber composite of the present invention in a dispersion medium is described below. The dispersion medium used as a component of the composition obtained by dispersing the solid-phase cellulose nanofiber composite in a dispersion medium functions as a medium for dispersing the cellulose nanofibers, which are a component of the solid-phase cellulose nanofiber composite, in the composition, and also functions as a medium for dissolving the cellulose derivative, which is a component of the solid-phase cellulose nanofiber composite. In the composition, the cellulose derivative is dissolved in the dispersion medium, and the cellulose nanofibers are dispersed in the dispersion medium, resulting in a state in which the cellulose derivative is coordinated to the cellulose nanofibers, and the cellulose nanofibers have excellent dispersibility in the composition.

[0046] Examples of the dispersion medium include organic solvents. Examples of the organic solvent include alcohols having 1 to 5 carbon atoms, such as tetrahydrofuran, acetone, ethanol, and propanol, cyclohexanol, propylene glycol, cyclohexanone, dioxane, cellosolve, butyl cellosolve, glacial acetic acid, formic acid, dimethylformamide (DMF), dimethyl sulfoxide (DMSO), pyridine, methylene chloride, chloroform, a mixture of benzene:methanol (1:1 (volume ratio)), a mixture of toluene:ethanol (3:2 (volume ratio)), and a mixture of glycerin:water (3:7 (volume ratio)). Examples of the dispersion medium include water. Any of these various dispersion media may be used alone, or two or more of them may be used in combination. Also, a solution in which organic solvents compatible with water are mixed at any ratio may be used as the dispersion liquid.

[0047] The amount of the dispersion medium used is not particularly limited and can be selected depending on the conditions of use of the solid-phase cellulose nanofiber composite of the present invention.

[0048] <Cellulose nanofiber molded products> The composition obtained by dispersing the solid-phase cellulose nanofiber composite of the present invention in a dispersion medium can be formed into a predetermined shape, and then the dispersion medium can be removed from the composition by drying or the like to obtain a cellulose nanofiber molded article of a predetermined shape. In the composition obtained by dispersing the solid-phase cellulose nanofiber composite of the present invention in a dispersion medium, the aggregation state of the cellulose nanofibers is reduced and the cellulose nanofibers are uniformly dispersed, so that the cellulose nanofiber molded article obtained by removing the dispersion medium from the composition has a uniform distribution of the cellulose nanofibers and a smooth surface. Furthermore, the composition obtained by dispersing the solid-phase cellulose nanofiber composite of the present invention in a dispersion medium has appropriate fluidity in addition to excellent dispersibility of the cellulose nanofibers, so that a film-shaped molded article can be easily obtained.

[0049] <Method for producing solid-phase cellulose nanofiber composite> The solid-phase cellulose nanofiber composite of the present invention can be produced, for example, by a cellulose nanofiber aqueous dispersion preparation step of preparing a cellulose nanofiber aqueous dispersion in which cellulose nanofibers are dispersed in water, a cellulose nanofiber and cellulose derivative-containing aqueous dispersion preparation step of adding a cellulose derivative to the cellulose nanofiber aqueous dispersion to prepare an aqueous dispersion containing cellulose nanofibers and cellulose derivatives, and a drying step of drying the cellulose nanofiber and cellulose derivative-containing aqueous dispersion. In the above-mentioned production method example, the cellulose derivative is added to the cellulose nanofiber aqueous dispersion to dissolve the cellulose derivative in the cellulose nanofiber aqueous dispersion, so that the cellulose derivative is physically adsorbed to the cellulose nanofibers to integrate the cellulose nanofibers and the cellulose derivatives, and then a drying process is performed to remove the water, which is the dispersion medium, to further promote the adsorption of the cellulose nanofibers and the cellulose derivative to produce a solid-phase cellulose nanofiber composite. An example of the drying step is a freeze-drying step in which the cellulose nanofiber and cellulose derivative-containing aqueous dispersion is freeze-dried.

[0050] An example of the cellulose nanofiber aqueous dispersion preparation process is a method of obtaining cellulose nanofibers by subjecting a cellulose precursor, which is a raw material derived from a natural product, to a defibration process to convert the cellulose precursor into nanofibers. The method of defibrating the cellulose precursor is not particularly limited, and examples include defibration processes using a mixer, a high-speed homomixer, an ultrasonic homogenizer, a low-pressure homogenizer, a high-pressure homogenizer, a high-speed rotating mixer, a grinder, freeze grinding, a media mill, a ball mill, etc. EXAMPLES

[0051] Next, examples of the present invention will be described, but the present invention is not limited to these examples as long as they do not depart from the spirit of the present invention.

[0052] <Preparation of solid-phase cellulose nanofiber composite> Example 1 A cellulose nanofiber and cellulose derivative-containing aqueous dispersion was prepared by adding 0.01 g of powdered hydroxypropyl cellulose (cellulose derivative) (mass ratio of cellulose nanofiber:hydroxypropyl cellulose = 1:0.1) to a cellulose nanofiber aqueous dispersion (0.1 g of cellulose nanofiber, average fiber length 100 μm, average fiber diameter 30 to 40 nm, Mori Machinery Corporation's "CellFim C-100 (water content approximately 95 mass%)") and stirring until the hydroxypropyl cellulose was dissolved. The resulting cellulose nanofiber and cellulose derivative-containing aqueous dispersion was frozen with liquid nitrogen and then dried to prepare a solid-phase cellulose nanofiber composite in which the cellulose nanofiber and cellulose derivative were integrated.

[0053] Example 2 A solid-phase cellulose nanofiber composite in which cellulose nanofibers and cellulose derivatives were integrated was prepared in the same manner as in Example 1, except that 0.05 g of powdered hydroxypropyl cellulose (cellulose derivative) was added (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:0.5).

[0054] Example 3 A solid-phase cellulose nanofiber composite in which cellulose nanofibers and cellulose derivatives were integrated was prepared in the same manner as in Example 1, except that 0.1 g of powdered hydroxypropyl cellulose (cellulose derivative) was added (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:1).

[0055] Example 4 A solid-phase cellulose nanofiber composite in which cellulose nanofibers and cellulose derivatives were integrated was prepared in the same manner as in Example 1, except that 0.3 g of powdered hydroxypropyl cellulose (cellulose derivative) was added (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:3).

[0056] Example 5 A solid-phase cellulose nanofiber composite in which cellulose nanofibers and cellulose derivatives were integrated was prepared in the same manner as in Example 1, except that 0.5 g of powdered hydroxypropyl cellulose (cellulose derivative) was added (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:5).

[0057] Example 6 A solid-phase cellulose nanofiber composite in which cellulose nanofibers and cellulose derivatives were integrated was prepared in the same manner as in Example 1, except that 1.0 g of powdered hydroxypropyl cellulose (cellulose derivative) was added (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:10).

[0058] Example 7 A solid-phase cellulose nanofiber composite in which cellulose nanofibers and cellulose derivatives were integrated was prepared in the same manner as in Example 1, except that 2.0 g of powdered hydroxypropyl cellulose (cellulose derivative) was added (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:20).

[0059] Comparative Example 1 Solid-phase cellulose nanofibers were prepared in the same manner as in Example 1, except that hydroxypropyl cellulose (a cellulose derivative) was not added.

[0060] <Evaluation items> (1) Handling of solid-phase cellulose nanofiber composites 20 ml of tetrahydrofuran was placed in a transparent test container, and while stirring with a stirrer at 1000 rpm, the solid-phase cellulose nanofiber composites of Examples 1 to 7 and the solid-phase cellulose nanofibers of Comparative Example 1 were added to the tetrahydrofuran so that the amount of cellulose nanofiber was 0.1 g. The time required from the addition of the solid-phase cellulose nanofiber composite until the cellulose nanofiber composite was uniformly dispersed was measured and evaluated as follows, with △ or higher being considered as passing. It was visually determined that the cellulose nanofiber composite was uniformly dispersed in tetrahydrofuran. ◎: The cellulose nanofiber composite was uniformly dispersed within 1.0 hour. ○: The cellulose nanofiber composite was uniformly dispersed within more than 1.0 hours and less than 2.0 hours. △: The cellulose nanofiber composite was uniformly dispersed within more than 2.0 hours and within 5.0 hours. ×: The cellulose nanofiber composite is not uniformly dispersed within 5.0 hours.

[0061] As a reference example 1 in which the cellulose nanofibers and the cellulose derivatives were not integrated, a cellulose nanofiber aqueous dispersion (average fiber length 100 μm, average fiber diameter 30-40 nm, "CellFim C-100 (water content approximately 95% by mass)" manufactured by Mori Machinery Corporation) was frozen in liquid nitrogen and then dried to remove water from the cellulose nanofiber aqueous dispersion to obtain solid-phase cellulose nanofibers. 0.05 g of hydroxypropyl cellulose and 0.1 g of the solid-phase cellulose nanofibers obtained as described above (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:0.5) were added to 20 ml of tetrahydrofuran, and the time required for the solid-phase cellulose nanofibers to be uniformly dispersed was measured while stirring at a rotation speed of 1000 rpm using a stirrer.

[0062] In addition, as Reference Example 2 in which the cellulose nanofibers and cellulose derivatives were not integrated, 0.5 g of hydroxypropyl cellulose and 0.1 g of the solid-phase cellulose nanofibers obtained as described above (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:5) were added to 20 ml of tetrahydrofuran, and the time required for the solid-phase cellulose nanofibers to be uniformly dispersed was measured while stirring at a rotation speed of 1000 rpm using a stirrer.

[0063] In addition, as Reference Example 3 in which the cellulose nanofibers and cellulose derivatives were not integrated, 1.0 g of hydroxypropyl cellulose and 0.1 g of the solid-phase cellulose nanofibers obtained as described above (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:10) were added to 20 ml of tetrahydrofuran, and the time required for the solid-phase cellulose nanofibers to be uniformly dispersed was measured while stirring at a rotation speed of 1000 rpm using a stirrer.

[0064] (2) Dispersibility of cellulose nanofiber composite in the solid phase 20 ml of tetrahydrofuran was added to a transparent test container, and then the solid-phase cellulose nanofiber composites of Examples 1 to 7 and the solid-phase cellulose nanofibers of Comparative Example 1 were added to the tetrahydrofuran so that the amount of cellulose nanofiber was 0.1 g, and the mixture was stirred at 1000 rpm using a stirrer for 24 hours to prepare Dispersion 1. Then, 0.5 ml of Dispersion 1 was taken in a transparent test container, and 6 ml of tetrahydrofuran was added to prepare Dispersion 2 for dispersibility evaluation, and the dispersion state of the cellulose nanofibers was visually observed and evaluated as follows, with ○ or higher being considered a pass. ◎: The dispersion state of cellulose nanofibers is excellent. ◯: Some aggregation of cellulose nanofibers is observed, but the dispersion is good. ×: Most of the cellulose nanofibers are in an aggregated state, and no dispersibility of the cellulose nanofibers is observed.

[0065] In addition, as Reference Example 4 in which the cellulose nanofibers and the cellulose derivatives are not integrated, a cellulose nanofiber aqueous dispersion (average fiber length 100 μm, average fiber diameter 30-40 nm, "CellFim C-100 (water content about 95 mass%)" manufactured by Mori Machinery Co., Ltd.) was dried to remove water from the cellulose nanofiber aqueous dispersion to obtain solid-phase cellulose nanofibers, and 0.1 g of hydroxypropyl cellulose and 0.1 g of the solid-phase cellulose nanofibers obtained as described above (mass ratio of cellulose nanofibers: hydroxypropyl cellulose = 1:1) were added to 20 ml of tetrahydrofuran, and the mixture was stirred at a rotation speed of 1000 rpm for 24 hours to prepare a cellulose nanofiber composition, which is a dispersion of cellulose nanofibers. 0.5 ml of this cellulose nanofiber composition was taken in a transparent test container, and 6 ml of tetrahydrofuran was added to prepare dispersion 2 for dispersibility evaluation.

[0066] (3) Transmittance of light with a wavelength of 400 nm 20 ml of tetrahydrofuran was added to a transparent test container, and the solid-phase cellulose nanofiber composites of Examples 1 to 7 and the solid-phase cellulose nanofibers of Comparative Example 1 were added to tetrahydrofuran so that the amount of cellulose nanofibers was 0.1 g. The mixture was stirred at 1000 rpm for 24 hours using a stirrer at 25°C to prepare dispersion 3. 2.0 ml of dispersion 3 was added to a 4.5 ml container, and the mixture was stirred at 1000 rpm using a stirrer with a diameter of 9 mm and a height of 6.5 mm under the condition of 25°C. Light with a wavelength of 400 nm was irradiated to the center of the height direction of dispersion 3 during stirring with an optical path length of 1 cm, and the transmittance of light with a wavelength of 400 nm was measured from the radiant intensity (I0) of the incident light and the radiant intensity (I) of the light transmitted through the cellulose nanofiber composition. The measured value of the transmittance was calculated as the average value (average transmittance) of the transmittances measured every 2 seconds for 180 seconds from the start of stirring. This was repeated three times, and the average value of the average transmittance (n=3) obtained was taken as the transmittance of light with a wavelength of 400 nm.

[0067] (4) Standard deviation of transmittance The standard deviation was calculated for one average transmittance measurement taken every two seconds for 180 seconds, and the standard deviation of the transmittance was calculated from the average value of each standard deviation obtained from the three average transmittance measurements.

[0068] The evaluation results are shown in Table 1 below. FIG. 1 is a photograph showing the dispersibility of the solid-phase cellulose nanofiber composites in Comparative Example 1 (left), Example 1 (center), and Example 2 (right). FIG. 2 is a photograph showing the dispersibility of the solid-phase cellulose nanofiber composites in Comparative Example 1 (left), Example 3 (center), and Example 4 (right). FIG. 3 is a photograph showing the dispersibility of the solid-phase cellulose nanofiber composites in Comparative Example 1 (left), Example 5 (center), and Example 6 (right). FIG. 4 is a photograph showing the dispersibility of the solid-phase cellulose nanofiber composites in Comparative Example 1 (left) and Example 7 (right). FIG. 5 is a photograph showing the dispersibility of the cellulose nanofibers in Reference Example 4.

[0069] [Table 1]

[0070] 1 to 4, the cellulose nanofiber composites of Examples 1 to 7, in which the cellulose nanofibers and the cellulose derivatives are integrated into a solid phase, were rated as "◎" for handleability and quickly dispersed uniformly in the dispersion medium, so that they had handleability in the dispersion medium, and were also rated as "○" or better, showing excellent dispersibility in the dispersion medium. In particular, in Examples 2 to 7, in which the mass ratio of cellulose nanofibers:hydroxypropyl cellulose was in the range of 1:0.5 to 20, the dispersibility was rated as "◎", showing further improved dispersibility in the dispersion medium.

[0071] In addition, in the solid-phase cellulose nanofiber composites of Examples 1 to 7 in which the cellulose nanofibers and the cellulose derivatives are integrated, the standard deviation in the transmittance test was 0.10 or less, and the uniform dispersion in the dispersion medium was excellent. In particular, in Examples 4 to 7 in which the mass ratio of cellulose nanofiber:hydroxypropyl cellulose was in the range of 1:3 to 20, the standard deviation in the transmittance test was 0.01 or less, and the uniform dispersion in the dispersion medium was further improved. In addition, in the solid-phase cellulose nanofiber composites of Examples 1 to 7 in which the cellulose nanofibers and the cellulose derivatives are integrated, the transmittance of light with a wavelength of 400 nm was 0.3% or less, and the uniform dispersion in the dispersion medium was excellent.

[0072] Also, from Table 1, the solid-phase cellulose nanofiber composite in which the cellulose nanofiber and the cellulose derivative are integrated in Example 2 (mass ratio of cellulose nanofiber: hydroxypropyl cellulose = 1: 0.5) has further improved handleability compared to Reference Example 1 in which the cellulose nanofiber and the cellulose derivative are not integrated (mass ratio of cellulose nanofiber: hydroxypropyl cellulose = 1: 0.5). Also, the solid-phase cellulose nanofiber composite in which the cellulose nanofiber and the cellulose derivative are integrated in Example 5 (mass ratio of cellulose nanofiber: hydroxypropyl cellulose = 1: 5) has further improved handleability compared to Reference Example 2 in which the cellulose nanofiber and the cellulose derivative are not integrated (mass ratio of cellulose nanofiber: hydroxypropyl cellulose = 1: 5). Furthermore, the solid-phase cellulose nanofiber composite in which the cellulose nanofiber and the cellulose derivative are integrated in Example 6 (mass ratio of cellulose nanofiber: hydroxypropyl cellulose = 1: 10) has further improved handleability compared to Reference Example 3 in which the cellulose nanofiber and the cellulose derivative are not integrated (mass ratio of cellulose nanofiber: hydroxypropyl cellulose = 1: 10).

[0073] Furthermore, as can be seen from Figures 2 and 5, the solid-phase cellulose nanofiber composite in Example 3 in which the cellulose nanofibers and cellulose derivatives are integrated (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:1) has improved uniform dispersion in the dispersion medium compared to Reference Example 4 in which the cellulose nanofibers and cellulose derivatives are not integrated (mass ratio of cellulose nanofibers:hydroxypropyl cellulose = 1:1).

[0074] 1 to 4, the solid-phase cellulose nanofibers of Comparative Example 1, to which no cellulose derivative was added, could not be dispersed uniformly in the dispersion medium quickly, did not have handleability in the dispersion medium, and did not achieve dispersibility in the dispersion medium. Furthermore, in Comparative Example 1, the standard deviation of the transmittance test was 2.1, and the transmittance of light with a wavelength of 400 nm was 1.536%, indicating that uniform dispersion in the dispersion medium was not achieved. [Industrial Applicability]

[0075] The solid-phase cellulose nanofiber composite of the present invention has cellulose nanofibers, which are components of the solid-phase cellulose nanofiber composite, that have excellent dispersibility in dispersion media and can be easily handled in dispersion media, allowing the range of application of the cellulose nanofiber to be easily expanded, and therefore can be used in a wide range of fields, such as the field of resin compositions that are used as materials for molded products.

Claims

1. A cellulose nanofiber composite comprising a cellulose nanofiber and a cellulose derivative, A solid-phase cellulose nanofiber composite in which the cellulose nanofibers and the cellulose derivative are integrated together.

2. The solid-phase cellulose nanofiber composite according to claim 1 , wherein the cellulose derivative is physically adsorbed and integrated onto the cellulose nanofiber.

3. The solid-phase cellulose nanofiber composite according to claim 1 or 2, wherein the cellulose nanofibers in a dry state and the cellulose derivative are integrated together.

4. The solid-phase cellulose nanofiber composite according to claim 1 or 2, comprising 5.0 parts by mass or more and 5,000 parts by mass or less of the cellulose derivative relative to 100 parts by mass of the cellulose nanofiber.

5. The cellulose nanofiber composite according to claim 1 or 2, comprising 10 parts by mass or more and 2,000 parts by mass or less of the cellulose derivative per 100 parts by mass of the cellulose nanofiber.

6. 3. A solid-phase cellulose nanofiber composite as described in claim 1 or 2, wherein the standard deviation in a transmittance test for light with a wavelength of 400 nm measured every 2 seconds over a period of 180 seconds for the solid-phase cellulose nanofiber composite containing 10 parts by mass or more and 2,000 parts by mass or less of the cellulose derivative per 100 parts by mass of the cellulose nanofiber is 0.10 or less.

7. The solid-phase cellulose nanofiber composite according to claim 1 or 2, wherein the cellulose derivative comprises at least one selected from the group consisting of hydroxyalkyl cellulose and alkyl cellulose.

8. The solid-phase cellulose nanofiber composite according to claim 1 or 2, wherein the cellulose derivative is a hydroxyalkyl cellulose.

9. The solid-phase cellulose nanofiber composite according to claim 8, wherein the hydroxyalkyl cellulose is hydroxypropyl cellulose.

Citation Information

Patent Citations

  • Gas barrier material, method for producing the same, and gas barrier film

    JP2016011392A

  • Derivatized CNF, method for producing same, and polyolefin resin composition

    WO2016010016A1